Lipoprotein lipase transport in plasma: role of muscle and adipose tissues in regulation of plasma lipoprotein lipase concentrations. - Karpe, F; Olivecrona, T; Olivecrona, G; Samra, J; Summers, L; Humphreys, S; Frayn, K (1998)
Lipoprotein lipase (LPL) is synthesized in tissues involved in fatty acid metabolism such as muscle and adipose tissue. LPL is also found in the circulation, but is mostly lipolytically inactive. The proportion of active circulating LPL increases after a fatty meal. We investigated the release of active and inactive LPL from adipose tissue and muscle in the fasting and postprandial states. Arteriovenous concentration gradients of LPL across adipose tissue and forearm muscle were measured in male subjects before and after a fat-rich meal (n = 7) and before and during infusion of a triacylglycerol emulsion (Intralipid) (n = 6). Plasma LPL activity rose after the meal and more so during Intralipid infusion. Plasma LPL mass (>95% inactive LPL) increased after the meal but decreased after Intralipid infusion. In the fasting state (n = 13) muscle efflux of LPL activity was 0.263 +/- 0.098 mU/min per 100 ml of muscle tissue whereas there was an influx of LPL activity to adipose tissue of 0.085 +/- 0.100 mU/min per 100 g of adipose tissue (P < 0. 02 muscle vs. adipose tissue). Similarly in the postprandial state only muscle released LPL activity. Both tissues released LPL mass. In the fasting state efflux was 17.8 +/- 8.8 ng/min per 100 ml muscle and 55.2 +/- 21.3 ng/min per 100 g of adipose tissue (P < 0. 05 muscle vs. adipose tissue). Release of LPL, either active or inactive, was not correlated with levels of non-esterified fatty acids or plasma triacylglycerol. In conclusion, there is a substantial release of LPL from adipose tissue and muscle, most of which is inactive. A small proportion of active LPL seems to be redistributed from muscle to adipose tissue.